Modernity, (Post)modernism and New Horizons of Postcolonial Studies. The Role and Direction of Caribbean Writing and Criticism in the Twenty-first Century - Penier, Izabella (International Studies. Interdisciplinary Political and Cultural Journal, 2012)
My article will take issue with some of the scholarship on current and prospective configurations of the Caribbean and, in more general terms, postcolonial literary criticism. It will give an account of the turn-of-the century debates about literary value and critical practice and analyze how contemporary fiction by Caribbean female writers responds to the socioeconomic reality that came into being with the rise of globalization and neo-liberalism. I will use David Scott’s thought provoking study-Refashioning Futures: Criticism after Postcoloniality (1999)-to outline the history of the Caribbean literary discourse and to try to rethink the strategic goals of postcolonial criticism.